Physical Performance and Quality of Life after Ankle Fusion - Harrasser, Norbert; Gebhardt, Christine; Südkamp, Norbert P.; Schmal, Hagen; Walther, Markus; Mehlhorn, Alexander Thomas (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Introduction Ankle fusion is still considered as an established therapy for end-stage ankle osteoarthritis. To determine exact description of postoperative functioning, it is necessary to consult a variety of functional scores and quality of life questionnaires.Methods/Patients 34 patients with 34 ankle fusions were investigated on average 5.9 years postoperatively by functional tests and health-related quality of life questionnaires (AOFAS hindfoot score [AOFAS: American Orthopaedic Foot/Ankle Society], Foot Function Index [FFI], Lower Extremity Functional Scale [LEFS], Lower Extremity Activity Scale [LEAS], Visual Analogue Scale Foot/Ankle Surgery [VAS FA], Short Form 36 [SF-36], EuroQol 5D [EQ-5D]).Results After ankle fusion: the majority of cases gain pain reduction, but residual symptoms may persist; the maximum walking distance (subjectively more than objectively) will be extended; rarely walking without any aids can be achieved; in most cases, the gait pattern is only slightly changed; the re-entry into working life is often possible; climbing stairs without any restrictions is not always possible; the psychological situation will be equalized with that of healthy people.Conclusion The results of the study confirm the success rates of ankle fusions in the majority of cases. Well defined limitations and residual symptoms can be named on the basis of the available data.Einleitung Die obere Sprunggelenkarthrodese (OSG-Arthrodese) gilt nach wie vor als etablierte Therapie der endgradigen OSG-Arthrose. Zur exakten Darstellung der postoperativen Funktionsfähigkeit ist es nötig eine Vielzahl an funktionellen Scores und Fragebögen zur Lebensqualität zur Rate zu ziehen.Methodik/Patienten 34 Patienten mit 34 OSG-Arthrodesen wurden im Mittel 5,9 Jahre postoperativ durch funktionelle Tests und mit Fragebögen zur gesundheitsbezogenen Lebensqualität (AOFAS-Rückfußscore [AOFAS: American Orthopaedic Foot/Ankle Society], Foot-Function-Index [FFI], Lower Extremity Functional Scale [LEFS], Lower Extremity Activity Scale [LEAS], Visual Analogue Scale Foot/Ankle Surgery [VAS FA], Short Form 36 [SF-36], EuroQol 5D [EQ-5D]) nachuntersucht.Ergebnisse Durch die OSG-Arthrodese konnte: in der Mehrzahl der Fälle eine Schmerzreduktion, jedoch meist keine vollständige Schmerzfreiheit erreicht werden; die maximale Gehstrecke (subjektiv mehr als objektiv) verlängert werden; selten ein Gehen ohne jegliche Hilfsmittel erreicht werden; sich das Gangbild in den meisten Fällen objektiv nur sehr leicht verändern; der Wiedereinstieg ins Berufsleben oft ermöglicht werden; das Treppensteigen nicht immer problemlos ermöglicht werden; die psychische Situation mit derjenigen fußgesunder Personen angeglichen werden.Schlussfolgerung Die Ergebnisse der Studie belegen den Erfolg der OSG-Arthrodese in der Mehrzahl der Fälle. Konkrete Einschränkungen und Restbeschwerden können den Patienten anhand der vorliegenden Daten genannt werden.
Keywords: osteoarthritis; foot; functional follow-up